Cirurgia bariátrica (Fobi capella) e gastrectomias: custos e mortalidade no Brasil pelo DataSUS - ROCHA, Álvaro Brandão Menezes (2023)
Obesity is considered a chronic non-communicable disease, consisting of one of the main public health problems today, with its prevalence increasing rapidly and significantly in recent decades, with a series of deleterious repercussions with increased morbidity and mortality. In this context, the surgical approach is one of the therapies of choice. Among the various surgical techniques, the Roux-en-Y gastric bypass is the most performed worldwide, corresponding to about 45% of total procedures, and is also the most costly from a financial point of view. In Brazil, the medical literature still lacks studies that analyze and compare the costs and mortality of these surgical procedures. Based on these data, the present research aims to study the financial data and mortality rates involving total and vertical gastrectomy surgeries notified and registered nationally in the Unified Health System. Cases of patients undergoing medical procedures categorized as digestive tract surgery were analyzed, with 2,118 hospital admissions for laparoscopic bariatric surgery in Brazil between 2017 and 2020 recorded. The Northeast and Southeast regions have the most expenses related to procedures, corresponding to 75.56% of all expenses. The North, on the other hand, accounts for just 1% of all expenditures. The total expense for the treatment of complications after bariatric surgery was R$1,415,240.00 reais in the years analyzed. The South region was responsible for 83.94% of expenditures, the Northeast for 3.97%. The total number of deaths, 78.57% occurred in the South region, followed by the Southeast region with 16.67%. The highest mortality rate occurred in the State of São Paulo with 10.34. It is concluded that there is a greater concentration of the absolute number of procedures in the Northeast, and there are more hospitalizations for Videolaparoscopy than Sleeve Gastrectomy, and as for the cost, it was noted that the Northeast and Southeast regions have the most expenses, whereas the mortality rate is led by the South and Southeast regions.